Physiological screening for drought-tolerance traits among hemp (Cannabis sativa L.) cultivars in controlled environments and in field. Issue 6 (2nd November 2021) - Sheldon, Kendall; Shekoofa, Avat; Walker, Eric; Kelly, Heather
ABSTRACT: The identification of genetic traits that enable water conservation could improve water availability for plant use when drought may develop. Hemp (Cannabis sativa L.) production in the USA has continued to increase dramatically after the federal government legalized its cultivation in 2014, but because of strict regulations in the past, necessary research for identifying adapted cultivars with desirable traits is lacking. The objectives of this study were to identify water-saving traits among hemp cultivars and determine if they influence cannabidiol (CBD) potency. Three approaches were taken: (i) hemp cultivars transpiration rate (TR) responses to soil drying were evaluated in a greenhouse, (ii) Sensitivity of cultivars TR to high vapor pressure deficit (VPD) was tested in a walk-in chamber, (iii) Field trial data were examined to determine if expression of drought-tolerance traits was associated with changes in CBD potency. Five out of thirteen cultivars had the earliest stomatal closure at rates higher than fraction of transpirable soil water (FTSW) threshold of 0.55. Four out of twelve expressed the limited transpiration rate (TRlim) trait, with their VPD thresholds ranging from 1.2 to 2.6 kPa. Cultivar Ha3ze showed a desired early decrease in TR during soil drying, delayed wilting in the field when soil-water deficit developed, and had greater CBD percentage than other cultivars. This study provides useful information on variability among hemp cultivars in TR response to soil drying and high evaporative demand that can be applied in developing cultivars that are better suited to a range of water-limited conditions. Abbreviations: CBD, Cannabidiol; Cherry NT, Cherry Not Topped; Cherry T, Cherry Topped; DAT, Days after transplant; FTSW, Fraction of transpirable soil water; RWC, Relative water content; SLA, Specific leaf area; T1 NT, T1 Not Topped; TRlim, Limited transpiration rate; TR, Transpiration Rate; T1 T, T1 Topped; VPD, Vapor pressure deficit; WS, Wilting score